The Role of Modern Technologies in Teaching the Mother Tongue - Nisanbaeva Akmaral Kaldibaevna (Genius Journals, 2023)
This article discusses the role of modern technologies in teaching the mother tongue. Language is not merely a tool for communication; it is the essence of cultural identity and heritage. In an increasingly globalized world, preserving and teaching one's mother tongue has become a vital endeavor. Modern technologies, ranging from interactive apps to virtual classrooms, have revolutionized the process of language education
Keywords: Mother tongue teaching; modern technologies